The role of Fumonisins in the biological interaction between Fusarium verticillioides and Sitophilus zeamais - Usseglio, Virginia Lara (2020)
The aim of the current study was to investigate the entomopathogenic capacity of the mold Fusarium verticillioides and the effect of its mycotoxins fumonisins, on the grain beetle Sitophilus zeamais. We evaluated the capacity of this fungus to infect live insects, the antifungal activity of constituents of the insect’s epicuticle, and the effect of a fumonisin extract on the fitness of the insects. We found that F. verticillioides could not penetrate the cuticle of S. zeamais and that the fumonisin extract had no negative effects on the fitness of the insects. However, the progeny of the insects increased, and the fumonisin extract had repellent effects. This is the first report about the effects of fumonisins on the relationship between F. verticillioides and S. zeamais, which may provide useful information about interactions between pathogenic microorganisms and insects, especially on stored product pests.